Efeito da Somatotrofina Suína (pST) sobre o desenvolvimento testicular, idade à puberdade e qualidade espermática de machos suínos - Rabassa, Viviane Rohrig (2012)
The somatotropin (ST), which has its effects mediated by insulin-like growth factor I, has positive effects on gametogenesis and steroidogenesis, and can be used as an alternative treatment for infertile men. Exogenous somatotropin supplementation improves testicular development, gametogenesis and steroidogenesis, anticipating onset of puberty. However, no studies aiming to determine the mechanisms of action of this hormone on testicular function and age at puberty in healthy young boars were performed. Thus the hypothesis of this study were: 1) prepubertal male pigs receiving exogenous ST have accelerated testicular growth due to the mitogenic actions of IGF-I; 2) an increase in gametogenesis and teroidogenesis with consequent antecipation of age at puberty and 3) improvement of semen quality after the establishment of puberty. To confirm this hypothesis four experiments were performed. The Experiment 1 aimed to determine the interval between applications of porcine ST (pST), based on the determination of IGF-I. Experiment 2 aimed to measure the proliferation of testes cells in boars subjected to pST administration, as well as its effect on the metabolism. In Experiment 1, the mean concentration of serum IGF-I for pST Group was higher (P<0.05) than for Control Group, with differences between groups within the first three days after injection, determining the interval between injection to be used in the following experiments. In Experiment 2 there was a increase in the testicular weight (P=0.06) in pST Group, but a decrease in the number of seminiferous tubules and sertoli cells in this group (P<0.05). Experiment 3 aimed to determine the effect of pST administration during the prepubertal period on the metabolic profile, testicular development and anticipation of the sexual maturity. The pST Group had higher circulating concentration of testosterone after five months of age (P<0.05), which was concomitant with the onset of reproductive activity. These boars also had higher libido (P<0.05). The Experiment 4 aimed to determine the effect of pST on the semen quality after the establishment of puberty. It was observed an increase in vigor, volume, total sperm concentration and total number of inseminating doses (P<0.05). Still, the pST Group had a higher testicular weight at 12 months of age (P<0.05). In conclusion, the use of pST in young pigs is present positive effects on the testicular development, testosterone levels, libido and semen quality after the establishment of puberty. an alternative to increase reproductive efficiency, increasing the semen quality and the number of inseminating doses produced from one ejaculate.